ANALISIS PENGARUH KEPEMILIKAN MANAJERIAL DAN KINERJA KEUANGAN TERHADAP KEBIJAKAN DIVIDEN: REVIEW LITERATURE MEDIA SOSIAL DAN SENTIMEN INVESTOR: STUDI EMPIRIS PADA PERUSAHAAN YANG MELAKUKAN IPO - Dedi Irawan; Hevi Oktiawati (Institut Agama Islam Agus Salim Metro Lampung, 2023)
Social media has given companies the opportunity to build their image and stimulate significant attention and positive emotional responses. Investors are also no longer passive participants; they can now communicate, comment, mention, react to information and express their sentiments/views, and the more companies come to public attention and media coverage, the more companies will be swayed by investors. The purpose of this study was to determine the effect of social media on investor sentiment in the Indonesian capital market, so that investors can get an overview of following the market and predicting stock returns and trading volume in the future. The results of the study show that neutral sentiment, negative sentiment, and positive sentiment on Instagram have no effect on stock returns. Neutral sentiment also has no effect on stock trading volume, while negative sentiment and positive sentiment have an effect on stock trading volume